Proceedings of the 17th ACM Great Lakes Symposium on VLSI 2007
DOI: 10.1145/1228784.1228838
|View full text |Cite
|
Sign up to set email alerts
|

Exploring subsets of standard cell libraries to exploit natural fault masking capabilities for reliable logic

Abstract: Deep submicron technology is expected to be plagued by many reliability issues including soft errors in logic. To address this, we demonstrate how exploiting the natural fault masking characteristics of logical functions can be achieved by exploring the design space for selecting subsets of cells from within a cell library prior to synthesis. Subset selection alone is shown to improve the reliability of combinational logic circuits by more than 35%. We compare how subset libraries effect the trade-offs between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The second stage consists of applying the threshold to create a suitable subset of robust cells. The usual tuning of a library creates a subset of cells by excluding complete cells [4,5,6]. In this approach, instead of removing a cell completely, a restriction on the look-up table is imposed.…”
Section: B Convolution Of Probability Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second stage consists of applying the threshold to create a suitable subset of robust cells. The usual tuning of a library creates a subset of cells by excluding complete cells [4,5,6]. In this approach, instead of removing a cell completely, a restriction on the look-up table is imposed.…”
Section: B Convolution Of Probability Distributionsmentioning
confidence: 99%
“…There are examples for which library tuning is used to reduce soft errors [4], here different subsets are generated and used in synthesis to analyze their behavior to soft errors. Library tuning as used in [5] is meant to iteratively remove cells from the library to pursue a synthesis speed-up.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is selected to apply the developed methodology and then obtain a new characterization. In this case, the selected library's name is SXLIB [3].…”
Section: Standard Cell Librarymentioning
confidence: 99%
“…In relation to the probability of a soft error being generated, cell supply voltage, sizing parameters, and transient waveform descriptions have been used to predict the resulting upset rate (Ness et al, 2007;Zhang and Wang, 2006). In relation to the probability that an error propagates, Krishnaswamy et al showed that the likelihood of an error propagating is directly related to signal observability and probability (Krishnaswamy et al, 2007).…”
Section: Reliabilitymentioning
confidence: 99%